2016
DOI: 10.1016/j.spinee.2016.07.531
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fusion rate and clinical results between CaO-SiO2-P2O5-B2O3 bioactive glass ceramics spacer with titanium cages in posterior lumbar interbody fusion

Abstract: In lumbar posterior interbody fusion surgery, CaO-SiO-PO-BO glass ceramics spacer showed a similar fusion rates and clinical outcomes compared with titanium cage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 22 publications
1
43
1
Order By: Relevance
“…In the previous study, we reported the efficacy and safety of BGS-7 spacers compared with autograft using titanium cages in the patients who required 1-level posterior lumbar interbody fusion (PLIF). 18 The BGS-7 spacers showed similar fusion rates and clinical outcomes as autograft using titanium cages, and the number of adverse events after surgery was similar for both groups. However, the previous study evaluated radiologic status for only 6 months and 1 year after the surgery, thereby lacking long-term results.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…In the previous study, we reported the efficacy and safety of BGS-7 spacers compared with autograft using titanium cages in the patients who required 1-level posterior lumbar interbody fusion (PLIF). 18 The BGS-7 spacers showed similar fusion rates and clinical outcomes as autograft using titanium cages, and the number of adverse events after surgery was similar for both groups. However, the previous study evaluated radiologic status for only 6 months and 1 year after the surgery, thereby lacking long-term results.…”
mentioning
confidence: 76%
“…The previous study was performed for the subjects at 4 institutions to evaluate whether the BGS-7 spacer (NovoMax; CGBio Inc., Seongnam, Korea) implantation is noninferior to the implantation of titanium alloy (Ti-6Al-4V) cages (4CIS; Solco Biomedical, Seoul, Korea) filled with autologous bone in 1-level PLIF for a year. 18 The study was conducted between October 28, 2010, and September 13, 2013, and was approved by the Institutional Review Board (IRB) of each institution. This study was carried out to assess changes in bone fusion rate and clinical results at follow-up for at least 48 months from the patients of the previous study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of enhanced titanium, additional bioactive glass ceramics, and other materials can reduce the rate of pseudoarthrosis. 31 Second, we need to preserve posterior support. Motion-preserving total disc replacement surgery showed more stable outcomes than the currently evaluated method 32 because of complete preservation of the posterior facet complex.…”
Section: How To Solve Issues and Gain Better Outcomesmentioning
confidence: 99%
“…First, we need to use more stable and advanced materials for interbody fusion. The use of enhanced titanium, additional bioactive glass ceramics, and other materials can reduce the rate of pseudoarthrosis [32]. Second, we need to preserve posterior support.…”
Section: How To Solve Issues and Gain Better Outcomesmentioning
confidence: 99%